2012
DOI: 10.1016/j.athoracsur.2011.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemoradiation Therapy Is Beneficial for Clinical Stage T2 N0 Esophageal Cancer Patients Due to Inaccurate Preoperative Staging

Abstract: Background It remains unclear if patients with clinical stage T2 N0 (cT2 N0) esophageal cancer should be offered induction therapy vs surgical intervention alone. Methods This was a retrospective cohort study of cT2 N0 patients undergoing induction therapy, followed by surgical resection, or resection alone, at the Johns Hopkins Hospital from 1989 to 2009. Kaplan-Meier analysis was used to compare all-cause mortality in cT2 N0 patients who had resection alone vs those who had induction chemoradiation therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 13 publications
3
66
0
Order By: Relevance
“…In fact, just 35 of the 59 patients receiving primary resection were correctly staged while 13 patients were over- und 11 patients were understaged. These findings are in line with other available studies analyzing the optimal treatment strategy in patients with cT2 tumors [5,6,7,8,9]. Indeed, Rice et al [5] showed in 61 cT2N0 esophageal cancer patients that just 13% of the study patients were staged correctly regarding the T category, while of the incorrectly staged patients 63% were over- and 37% were understaged.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In fact, just 35 of the 59 patients receiving primary resection were correctly staged while 13 patients were over- und 11 patients were understaged. These findings are in line with other available studies analyzing the optimal treatment strategy in patients with cT2 tumors [5,6,7,8,9]. Indeed, Rice et al [5] showed in 61 cT2N0 esophageal cancer patients that just 13% of the study patients were staged correctly regarding the T category, while of the incorrectly staged patients 63% were over- and 37% were understaged.…”
Section: Discussionsupporting
confidence: 79%
“…The working group revealed that the patients treated with trimodality therapy had an excellent overall survival with a high rate of complete pathologic response, providing support for multimodality therapy in patients with cT2 tumors. Similar recommendations were proposed by Zhang et al [9]. Indeed, in their retrospective analysis including 69 patients with cT2N0 esophageal cancer, they failed to show that induction therapy did translate into a statistically significant improvement of survival; nevertheless, the authors still recommend neoadjuvant therapy to all cT2N0 patients before surgery due to a significant understaging in this study [9].…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations